2020
DOI: 10.31557/apjcp.2020.21.9.2793
|View full text |Cite
|
Sign up to set email alerts
|

Coffee Consumption and Pancreatic Cancer Risk: A Meta-Epidemiological Study of Population-based Cohort Studies

Abstract: Objective: Previous systematic reviews evaluating the association between coffee consumption and pancreatic cancer showed inconsistent results. The aim was to conduct a meta-epidemiological study to explore further the association between coffee consumption and the incidence of pancreatic cancer. Methods: The selection criteria were defined as a population-based prospective cohort study reporting adjusted relative risk (RR) and their 95% confidence interval (95%CI) of pancreatic cancer occurrence according to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…In this study, we observed an inverse association between coffee consumption and the risk of pancreatic cancer, indicating that coffee could be a main contributor to the observed association of type 2 prevention diabetes diet with the risk of pancreatic cancer. Notably, the association of coffee consumption with the risk of pancreatic cancer has been debated for decades; however, most previous studies revealed a null association [37]. A recent prospective study of 193,439 subjects found that increased consumption of filtered coffee was associated with a reduced risk of pancreatic cancer (HR for 4 versus 1 cup/day: 0.74; 95% CI: 0.57, 0.95), while such an inverse association was not found for total and boiled coffee consumption [38].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we observed an inverse association between coffee consumption and the risk of pancreatic cancer, indicating that coffee could be a main contributor to the observed association of type 2 prevention diabetes diet with the risk of pancreatic cancer. Notably, the association of coffee consumption with the risk of pancreatic cancer has been debated for decades; however, most previous studies revealed a null association [37]. A recent prospective study of 193,439 subjects found that increased consumption of filtered coffee was associated with a reduced risk of pancreatic cancer (HR for 4 versus 1 cup/day: 0.74; 95% CI: 0.57, 0.95), while such an inverse association was not found for total and boiled coffee consumption [38].…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis by Gao et al examined 25 studies and showed that there was no appreciable link between fish intake and pancreatic cancer risk with an RR of 1.00 (95% CI: 0.93-1.07) [41]. A meta-analysis by Bae et al with twelve cohort studies and 10,587 pancreatic cancer incidents showed no increased risk of pancreatic cancer among patients with the highest versus the lowest level of coffee consumption with a summary RR of 0.98 (95% CI: 0.88-1.10) [38].…”
Section: Namazi Et Al [4]mentioning
confidence: 99%
“…Pancreatic cancer is a common malignant tumor in the clinic (1). Foreign investigation results show that pancreatic cancer ranks fourth in tumor mortality and is the digestive system tumor with the worst prognosis (2).…”
Section: Introductionmentioning
confidence: 99%